A Salvia miltiorrhiza ethanol extract ameliorates tissue destruction caused by experimental periodontitis in rats. (11th June 2015) - Chiang, C.‐Y.; Tsai, H.‐T.; Chang, W.‐L.; Chin, Y.‐T.; Chang, W.‐J.; Tu, H.‐P.; Chiu, H.‐C.; Fu, E.
Abstract : Background and Objective: Salvia miltiorrhiza Bunge (Labiatae), or Danshen, is a Chinese medicine used for treatment of cardiac diseases by improving blood circulation and inhibiting inflammatory responses. In this study, we aimed to determine whether an ethanol extract of S. miltiorrhiza can ameliorate tissue damage caused by periodontitis. Material and Methods: An ethanolic extract of S. miltiorrhiza roots was prepared, and its major constituents were determined by HPLC analysis, by comparison with known standards for the major bioactive components. The activity of the extract was evaluated in a rat model in which periodontitis was induced by ligation of a silk suture around the neck of molar teeth. The effects of the S. miltiorrhiza extract on periodontitis were assessed by dental radiography, micro‐computed tomography and histology. Results: The cemento–enamel junction–bone distances among the four different groups of rats were significantly different: the distance was shorter in groups treated with ligation + S. miltiorrhiza extract than in the group treated with ligation only, but was longer than in the nonligated group, regardless of the radiographic methods used. Histology and histometry also indicated a similar trend of less gingival inflammation and alveolar bone destruction in the histological sections from the S. miltiorrhiza extract groups than in those from the ligation group. Conclusion: Because the S. miltiorrhiza extract reduced tissue damage and bone loss caused by ligation‐induced periodontitis in rats, we suggest that the S. miltiorrhiza extract might have an ameliorative effect on periodontal tissue destruction during the process of periodontitis.